If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4c(a + -6) + 7(a + -6) = 0 Reorder the terms: 4c(-6 + a) + 7(a + -6) = 0 (-6 * 4c + a * 4c) + 7(a + -6) = 0 Reorder the terms: (4ac + -24c) + 7(a + -6) = 0 (4ac + -24c) + 7(a + -6) = 0 Reorder the terms: 4ac + -24c + 7(-6 + a) = 0 4ac + -24c + (-6 * 7 + a * 7) = 0 4ac + -24c + (-42 + 7a) = 0 Reorder the terms: -42 + 7a + 4ac + -24c = 0 Solving -42 + 7a + 4ac + -24c = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '42' to each side of the equation. -42 + 7a + 4ac + 42 + -24c = 0 + 42 Reorder the terms: -42 + 42 + 7a + 4ac + -24c = 0 + 42 Combine like terms: -42 + 42 = 0 0 + 7a + 4ac + -24c = 0 + 42 7a + 4ac + -24c = 0 + 42 Combine like terms: 0 + 42 = 42 7a + 4ac + -24c = 42 Add '24c' to each side of the equation. 7a + 4ac + -24c + 24c = 42 + 24c Combine like terms: -24c + 24c = 0 7a + 4ac + 0 = 42 + 24c 7a + 4ac = 42 + 24c Reorder the terms: -42 + 7a + 4ac + -24c = 42 + 24c + -42 + -24c Reorder the terms: -42 + 7a + 4ac + -24c = 42 + -42 + 24c + -24c Combine like terms: 42 + -42 = 0 -42 + 7a + 4ac + -24c = 0 + 24c + -24c -42 + 7a + 4ac + -24c = 24c + -24c Combine like terms: 24c + -24c = 0 -42 + 7a + 4ac + -24c = 0 The solution to this equation could not be determined.
| X+2x=1050 | | -6(-1)-2y=12 | | 8c-7c=16 | | 2x+6(1+5x)=230 | | (2x-7/4)=0 | | 25=k/5;k=5 | | x-3+2x=33 | | 8-5x=42 | | -2(3-5k)=-76 | | -5p-3(-p)-p=4 | | -7(x-7)=-84 | | .13x+14.95=.39x-15.00 | | Lg(3x-5)=-3 | | -5(3-7x)=-85 | | 4(-3m+2)=32 | | 40=32t | | 2n+8n-13=17 | | 1=w/6 | | (2v*3*4v)^4/2v^4 | | .39x-15.00=50 | | 5x-45=90 | | 5tanx+3=13 | | -4x+4=-4-4 | | 2m^2=784 | | -2=v/3 | | 11x-2x+68=11x+40 | | (2x+15)+(6x-37)=(6x+10) | | 3x-12+59=4x+20 | | 1.75x+0.75=4.75 | | 75x+255=1605 | | -4(6n-1)=100 | | 32+-4x=18+-2x |